+0  
 
0
42
2
avatar+2256 

Help 9,10

NotSoSmart  Mar 21, 2018
Sort: 

2+0 Answers

 #1
avatar+560 
+1

A and B

supermanaccz  Mar 21, 2018
 #2
avatar+85858 
+1

The equation is

 

( x - h)^2  + (y - k)^2  = r^2

 

Where  (h, k)  is the center and r is the radius

 

So  we have

 

(x - (-7) )^2  +  ( y  -  (-6) ) ^2  =  2^2

 

(x + 7)^2  + ( y + 6)^2  = 4 

 

 

10)   3 left, 4 up

 

The first equation  can be written as

 

(x - 0)^2  + (y - 0)^2  =  49     ⇒   center  =  (0, 0)

 

Moving to the left 3, we add 3 to the x coordinate of the center

Moving up 4, we subtract 4 from the y coordinate of the center 

 

( x - 0  + 3 )^2   + ( y - 0 - 4)^2  =  49

 

(x + 3)^2  + (y - 4)^2  = 49

 

 

cool cool cool

CPhill  Mar 21, 2018

17 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details